Some of my best friends : essays on lip service - Isen, Tajja (Atria/One Signal Publishers, 2022)
"A fearless and darkly comic essay collection about race, justice, and the limits of good intentions. In this stunning debut collection, Catapult editor-in-chief and award-winning voice actor Tajja Isen explores the absurdity of living in a world that has grown fluent in the language of social justice but doesn't always follow through. These nine daring essays explore the sometimes troubling and often awkward nature of that discord. Some of My Best Friends takes on the cartoon industry's pivot away from colorblind casting, the pursuit of diverse representation in the literary world, the law's refusal to see inequality, and the cozy fictions of nationalism. Isen deftly examines the quick, cosmetic fixes society makes to address systemic problems, and reveals the unexpected ways they can misfire. ...Isen interlaces cultural criticism with her lived experience to explore the gaps between what we say and what we do, what we do and what we value, what we value and what we demand."--Publisher's website.